80.9k views
4 votes
Find the value of the expression x3−y3+x2+y2+3 by substituting x=−2 and y=1.

2 Answers

4 votes

Answer: -1

Concept:

Here, we need to understand the idea of evaluation.

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given information

x = -2

y = 1

Given expression

x³ - y³ + x² + y² + 3

Substitute values into the expression

=(-2)³ - (1)³ + (-2)² + (1)² + 3

Simplify exponents

=-8 - 1 + 4 + 1 + 3

Simplify by simple operation (addition/subtraction)

=-9 + 4 + 1 + 3

=-5 + 1 + 3

=-4 + 3

=
\boxed {-1}

Hope this helps!! :)

Please let me know if you have any questions

User ATLUS
by
4.5k points
2 votes


\\ \sf\dashrightarrow x^3-y^3+x^2+y^2+3


\\ \sf\dashrightarrow (-2)^3-(1)^3+(-2)^2+(1)^2+3


\\ \sf\dashrightarrow -8-1+4+1+3


\\ \sf\dashrightarrow -9+8


\\ \sf\dashrightarrow -1

User Kolaente
by
4.5k points